A novel and environmentally friendly bioprocess for separation and partial purification of polysaccharides from Cordyceps sinensis mycelia by an aqueous two-phase system. Issue 60 (31st July 2017) - Li, Zhigang; Chen, Ailin; Li, Zhencheng; Qu, Man; Chen, Huayong; Yang, Bo; Wang, Yonghua
Abstract : An aqueous two-phase system comprising ethanol and salt not only could purify CS polysaccharides with high efficiency, but also simultaneously separated multiple active substances through coupling with ultrafiltration. Abstract : Separation and partial purification of polysaccharides from fungi or mushrooms are difficult and have become the main bottleneck in the development of a commercially viable process. In this study, an aqueous two-phase system (ATPS) composed of short chain alcohols and salts was developed for the separation and partial purification of polysaccharides and other bioactive constituents from Cordyceps sinensis (CS). The results showed that ATPS not only purified CS polysaccharides (CSPS) with the removal of 99.1% cell debris, 80% proteins, 90.7% pigments, and 61.3% nucleic acids, but also simultaneously recovered CSPS, adenosine, and mannitol up to 96.6%, 100%, and 88.4%, respectively. Compared with traditional purification methods, the coupling of ethanol/Na2 CO3 ATPS with ultrafiltration decreased the protein, nucleic acid, and pigment contents in the purified CSPS by 344%, 192%, and 290%, respectively. Therefore, this environmentally friendly method could have potential applications in large-scale separation of multiple bioactive constituents from fungi in the future.